Biokinetic Analysis of Arm Movement During the Shot Put and its Relationship to Throwing Distance Among Students - Muthanna Harith Ekrayyem (Program Studi Pendidikan Kepelatihan Olahraga, 2026)
This research aims to study the biomechanics of the shot put event and analyse the biomechanical variables influencing it, thereby providing coaches and athletes with an accurate scientific tool for performance evaluation and the identification of strengths and weaknesses. The shot put is an event that requires a high level of skill and physical fitness, particularly with the recent advancements in the use of modern imaging and analysis equipment. The research problem stems from the practical observation conducted by the researcher on students at the Faculty of Physical Education, which revealed a notable disparity in numerical results (distance achieved) in the shot put event, despite the relative similarity in the students’ physical composition. Hence, the research objectives were to identify certain biomechanical changes associated with shot put performance, and the researcher hypothesised the existence of a statistically significant relationship between performance level and the biomechanical variables studied. The research methodology and field procedures were then addressed, with the researcher adopting a descriptive approach using correlational methods due to its suitability for the nature of the problem; the research sample comprised 12 fourth-year students. The results were then presented and discussed, leading to a set of conclusions and recommendations. The results showed a statistically significant correlation between the take-off angle, take-off speed, take-off height, and the level of performance in the shot put. Consequently, the researcher recommended that further similar studies be conducted on other track and field events, emphasising the importance of taking these variables into account during training and instruction